2011
DOI: 10.1007/s10059-011-1055-x
|View full text |Cite
|
Sign up to set email alerts
|

Hypoxia Inducible Factor-1α Directly Induces the Expression of Receptor Activator of Nuclear Factor-κB Ligand in Periodontal Ligament Fibroblasts

Abstract: During orthodontic tooth movement, local hypoxia and enhanced osteoclastogenesis are observed in the compression side of periodontal tissues. The receptor activator of nuclear factor-κB ligand (RANKL) is an osteoblast/ stromal cell-derived factor that is essential for osteoclastogenesis. In this study, we examined the effect of hypoxia on RANKL expression in human periodontal ligament fibroblasts (PDLFs) to investigate the relationship between local hypoxia and enhanced osteoclastogenesis in the compression si… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
36
0

Year Published

2014
2014
2023
2023

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 47 publications
(39 citation statements)
references
References 33 publications
(34 reference statements)
3
36
0
Order By: Relevance
“…In addition, OPG is a decoy receptor for RANKL that regulates the functional state of RANKL [41]. A putative HIF-1α binding element resides at the RANKL promoter region [45] and induced HIF-1α was found to be associated with an increase in RANKL mRNA expression in intermittent hypoxia-exposed neuroblastoma cells. Earlier studies have shown that OPG expression level was down-regulated in hypoxic human oral squamous carcinoma cells and HIF-1α knock-down significantly increased OPG expression under hypoxic condition [46].…”
Section: Discussionmentioning
confidence: 99%
“…In addition, OPG is a decoy receptor for RANKL that regulates the functional state of RANKL [41]. A putative HIF-1α binding element resides at the RANKL promoter region [45] and induced HIF-1α was found to be associated with an increase in RANKL mRNA expression in intermittent hypoxia-exposed neuroblastoma cells. Earlier studies have shown that OPG expression level was down-regulated in hypoxic human oral squamous carcinoma cells and HIF-1α knock-down significantly increased OPG expression under hypoxic condition [46].…”
Section: Discussionmentioning
confidence: 99%
“…Consistent with our results, HIF-1 was recently found to directly enhance RANKL expression in PDLCs, which might promote OC differentiation. 11 Moreover, our group previously found that osteogenesis of PDLCs was improved when exposed to hypoxia. 17,18 Taken together, these findings suggest that hypoxia accelerates alveolar bone remodeling by promoting osteogenic differentiation of PDLCs as well as improving the RANKL/OPG ratio, which leads to enhanced osteoclastogenesis.…”
Section: Discussionmentioning
confidence: 98%
“…9,10 Recently, HIF-1a was found to up-regulate RANKL expression in PDLCs. 11 Moreover, treatment of the inhibitor of HIF-1a suppressed the rate of tooth movement. 12 These findings illustrate that oxygen tension might be involved in osteoclastogenesis during OTM.…”
Section: Introductionmentioning
confidence: 99%
“…Chromatin immunoprecipitation showed that HIF-1α binds to the receptor activator of the NF-κB ligand (RANKL) promoter region, and mutations of the putative HIF-1α binding site prevented hypoxia-induced RANKL transcriptional promotion, thus suggesting that HIF-1α mediates hypoxia-induced upregulation of RANKL expression and enhanced osteoclastogenesis [95]. Furthermore, it was reported that hypoxia triggered the diferentiation of peripheral mononuclear blood cells into functional osteoclasts in a HIF-dependent manner [96].…”
Section: Hif and Bone Homeostasismentioning
confidence: 99%